Nb–Al diffusion reaction in high Nb containing TiAl porous alloys. (August 2015) - Wang, F.; Liang, Y. F.; Shang, S. L.; Liu, Z. K.; Lin, J. P.
Abstract : High Nb containing TiAl porous alloys were synthesised by powder metallurgy (PM). In order to reveal reaction mechanism of Nb in preparation of the porous alloys, Nb–Al diffusion reaction was investigated using diffusion couples at relatively low temperatures of 600–800°C. The porous Nb–Al diffusion layer was identified as NbAl3 phase and the thickness of diffusion layer indicated that the Nb–Al diffusion mainly occurred at 800°C. In addition, the pore diameter distribution indicated that Nb–Al diffusion also contributed to the increase in pore diameter. According to these results, the diffusion reaction model was established for high Nb containing TiAl porous alloys.